The Nature of Trauma Informed Care in the Treatment of Men Convicted of a Sexual Offence With Trauma History - Senker, Sarah (Sexual offending, 2025)
Individuals who have committed sexual offences are more likely to have experienced trauma or childhood adversity than the general population (Kahn et al., 2021). Further, individuals who were convicted of a sexual offence perceive a strong connection between their own victimisation and their sexual offending (Grady et al., 2022). This initial scoping work, funded by the University of West England in the United Kingdom, involved in-depth qualitative interviews with 20 professionals and a roundtable including academics, policy makers and front-line practitioners from His Majesty’s Prison and Probation Service, NHS and third sector organisations. All participants had a history of working with individuals with a sexual conviction and a history of trauma or had been involved in academia in this area. The work identified an inconsistent use of the term ‘trauma informed’ across the sector and a gap in trauma informed care (TIC) for individuals with a ‘dual status’ as both a perpetrator of sexual abuse and victim of trauma. This was especially prominent for adult men relative to females or young people with sexual convictions. Individuals with a ‘dual status’ are particularly disadvantaged in having their trauma acknowledged and addressed if they are male. The extent that true TIC can be implemented across the justice system is challenged by the necessities of managing risk. Further research is required to better understand the experiences of people with lived experience and to explore the impact of TIC on reintegration and reoffending.